2020
DOI: 10.1097/inf.0000000000002763
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Acquisition of Cytomegalovirus Infection in Pregnancy Through Hygiene-based Behavioral Interventions: A Systematic Review and Gap Analysis

Abstract: BackgroundCongenital cytomegalovirus (cCMV) infection is the most common non-genetic cause of sensorineural hearing loss in childhood and an important cause of neuro-disability.There is no licensed CMV vaccine and no antenatal treatment for congenital CMV that is routinely recommended in clinical practice in the UK. ObjectivesTo review the published literature for studies that evaluated preventative hygienebased interventions in pregnancy for their impact on knowledge about CMV prevention, the uptake of preven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…Like most infectious diseases for which there are not yet vaccines, behavioral modifications do not completely eliminate the risk of cCMV. However, there is increasing evidence that antenatal education about cCMV and risk reduction strategies may significantly lower rates of antepartum seroconversion 6 …”
Section: Antenatal Counselingmentioning
confidence: 99%
See 3 more Smart Citations
“…Like most infectious diseases for which there are not yet vaccines, behavioral modifications do not completely eliminate the risk of cCMV. However, there is increasing evidence that antenatal education about cCMV and risk reduction strategies may significantly lower rates of antepartum seroconversion 6 …”
Section: Antenatal Counselingmentioning
confidence: 99%
“…A recent expert review published in the American Journal of Obstetrics and Gynecology highlighted cCMV prevention behaviors, specifically that “both parents avoid contact with body fluids from infected individuals, especially toddlers, from before conception until 14 weeks (gestation).” 8 Prenatal cCMV education has been found to be viewed favorably by women 17,18 and has been associated with increased engagement in recommended hygiene practices 19 . Observational controlled studies have found that hygiene counseling of CMV‐seronegative pregnant women significantly decreased risk of both seroconversion and congenital infection 6,17 . Some practitioners may not want to worry their patients by discussing the risks of cCMV, but these risks deserve consideration by expectant individuals.…”
Section: Antenatal Counselingmentioning
confidence: 99%
See 2 more Smart Citations
“…Antenatal education about CMV risk reduction may provide a significant opportunity to reduce CMV infection in pregnancy and consequently reduce the incidence of cCMV. In a recent systematic review, seven studies were identified which investigated preventative hygiene-based interventions in pregnancy or in women of child-bearing age [ 9 ]. This concluded that hygiene-based interventions in pregnancy could play a useful role in primary prevention of CMV infection in pregnancy, however the studies were too heterogeneous in terms of study population, intervention and outcome to form firm conclusions on the relative impact of such interventions.…”
Section: Introductionmentioning
confidence: 99%